IMPLEMENTASI TUGAS DAN WEWENANG KEPALA DESA BERDASARKAN UNDANG-UNDANG NO 6 TAHUN 2014 TENTANG DESA: (Studi Di Desa Rawan Kecamatan Krejengan Kabupaten Probolinggo) - ACH. SYAMSUL ASKANDAR; Ahmad Taufiq H. (JUSTNESS - Jurnal Hukun dan Agama, 2022)
Abstract The village is the smallest area within the scope of the government structure, throughout the course of the state administration of the Republic of Indonesia, the village has developed in various forms so that it needs to be protected and empowered to become strong, advanced, independent and democratic so that it can create a strong foundation in implementing governance and development towards village communities as the lowest government unit in Indonesia, its position and authority still raises many pros and cons. This is because the laws governing Regional Government and the new ones have not provided any firmness regarding the duties and authorities of the Village Head. The method used is an empirical legal study. Village administration is a subsystem of the government administration system, so that the village has the authority to regulate and manage the interests of its people. The implementation of village government is inseparable from the implementation of regional autonomy, the village government is the leading unit in service to the community and is a strategic milestone for the success of all programs. Based on this, the formulations discussed in this study are, firstly the implementation of the duties of the village head is vulnerable in realizing the objectives of the village head's authority, and secondly for the supervision of the implementation of the village head's duties which includes all efforts or activities to ensure and direct that the implementation of the tasks or work runs. properly. Keywords: Duties and authorities, Village Head, Law no. 6 Year 2014